Haematuria Increases Progression of Advanced Proteinuric Kidney Disease - Yuste, Claudia; Rubio-Navarro, Alfonso; Barraca, Daniel; Aragoncillo, Inés; Vega, Almudena; Abad, Soraya; Santos, Alba; Macias, Nicolás; Mahillo, Ignacio; Gutiérrez, Eduardo; Praga, Manuel; Egido, Jesús; et al. (PLOS ONE, 2015)
Background Haematuria has been traditionally considered as a benign hallmark of some glomerular diseases; however new studies show that haematuria may decrease renal function. Objective To determine the influence of haematuria on the rate of chronic kidney disease (CKD) progression in 71 proteinuric patients with advanced CKD (baseline eGFR <30 mL/min) during 12 months of follow-up. Results The mean rate of decline in eGFR was higher in patients with both haematuria and proteinuria (haemoproteinuria, HP, n=31) than in patients with proteinuria alone (P patients, n=40) (-3.8±8.9 vs 0.9±9.5 mL/min/1.73m2/year, p<0.05, respectively). The deleterious effect of haematuria on rate of decline in eGFR was observed in patients <65 years (-6.8±9.9 (HP) vs. 0.1±11.7 (P) mL/min/1.73m2/year, p<0.05), but not in patients >65 years (-1.2±6.8 (HP) vs. 1.5±7.7 (P) mL/min/1.73m2/year). Furthermore, the harmful effect of haematuria on eGFR slope was found patients with proteinuria >0.5 g/24 h (-5.8±6.4 (HP) vs. -1.37± 7.9 (P) mL/min/1.73m2/year, p<0.05), whereas no significant differences were found in patients with proteinuria < 0.5 g/24 h (-0.62±7.4 (HP) vs. 3.4±11.1 (P) mL/min/1.73m2/year). Multivariate analysis reported that presence of haematuria was significantly and independently associated with eGFR deterioration after adjusting for traditional risk factors, including age, serum phosphate, mean proteinuria and mean serum PTH (β=-4.316, p=0.025). Conclusions The presence of haematuria is closely associated with a faster decrease in renal function in advanced proteinuric CKD patients, especially in younger CKD patients with high proteinuria levels; therefore this high risk subgroup of patients would benefit of intensive medical surveillance and treatment.